Raman signatures of broken inversion symmetry and in‐plane anisotropy in type‐II Weyl semimetal candidate TaIrTe4 - Liu, Yinan (2019)
The layered ternary compound TaIrTe4 is an important candidate to host the recently predicted type‐II Weyl fermions. However, a direct and definitive proof of the absence of inversion symmetry in this material, a prerequisite for the existence of Weyl Fermions, has so far remained evasive. Herein, an unambiguous identification of the broken inversion symmetry in TaIrTe4 is established using angle‐resolved polarized Raman spectroscopy. Combining with high‐resolution transmission electron microscopy, an efficient and nondestructive recipe to determine the exact crystallographic orientation of TaIrTe4 crystals is demonstrated. Such technique could be extended to the fast identification and characterization of other type‐II Weyl fermions candidates. A surprisingly strong in‐plane electrical anisotropy in TaIrTe4 thin flakes is also revealed, up to 200% at 10 K, which is the strongest known electrical anisotropy for materials with comparable carrier density, notably in such good metals as copper and silver.